1980
DOI: 10.1042/cs0590029
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Transepithelial Potassium Movement in the Epithelium of Distal Colon in Man

Abstract: 1. Methods for studying the kinetics of movement of radioactive tracers across human distal colonic epithelium have been developed for use in vivo and applied to examination of transepithelial transfers of potassium. 2. During absorption of 43K from the lumen, two potassium pools, A and B, in the epithelium were identified, having mean turnover half-times of 16 and 87 min respectively. On average about 50% of the potassium lumen-to-plasma flux and most, if not all, of the potassium plasma-to-lumen flux took pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, the mechanism of potassium transport across this epithelium has been disputed. In some studies potassium secretion was greater than expected from transepithelial electrical or chemical driving forces (cf Archampong, Harris & Clark, 1972;Yorio & Bentley, 1977;Powell, 1979;Kermode & Edmonds, 1980;Kliger, Binder, Bastl & Hayslett, 1981), suggesting active transport mechanisms. In contrast other investigations have shown evidence against active potassium transport.…”
Section: Introductionmentioning
confidence: 94%
“…However, the mechanism of potassium transport across this epithelium has been disputed. In some studies potassium secretion was greater than expected from transepithelial electrical or chemical driving forces (cf Archampong, Harris & Clark, 1972;Yorio & Bentley, 1977;Powell, 1979;Kermode & Edmonds, 1980;Kliger, Binder, Bastl & Hayslett, 1981), suggesting active transport mechanisms. In contrast other investigations have shown evidence against active potassium transport.…”
Section: Introductionmentioning
confidence: 94%
“…It is likely that colonic potassium secretion in vivo reflects, at least in part, passive movement of potassium from plasma to lumen secondary to the high, lumen-negative pd. However, 43K tracer studies have suggested that the passive component may be relatively small (Kermode and Edmonds 1980), and intraluminal amiloride has been shown to have no effect on net potassium secretion in the proximal rectum despite decreasing transmucosal pd by 30% (SandIe et al 1986b). Microelectrode studies also indicate that paracellular pathways in human proximal and distal colonic epithelia possess no significant potassium selectivity (Sandie and McGlone 1987).…”
Section: Potassium Secretionmentioning
confidence: 93%